Effect of pterygium on corneal topography and astigmatism - Lornanthakul, Sudarat; Tananuvat, Napaporn (Biomedical Sciences and Clinical Medicine, 2017)
Abstract To study the effects of pterygium on corneal topography and astigmatism and to determine the critical pterygium size which induces signi fi cant astigmatism. Methods Thirty-three patients with unilateral primary pterygium were evaluated for pterygium morphology (22 women and 11 men with mean age of 56.2±10.9 years). An automated keratometer and an Orbscan II were used to evaluate corneal astigmatism, and the latter was also used to assess corneal topography. Results from the pterygium and contralateral eyes were compared. Results Mean corneal extension and width of the pterygia was 2.7±1.0 and 4.2±1.2 mm, respectively. With-the-rule astigmatism was the most common type (66.7%), followed by oblique (27.3%), and against-the-rule astigmatism (6.0%). The median (IQR) corneal astigmatism between the pterygium and contralateral eyes as measured by auto-keratometry and Orbscan II including auto-K, sim-K, K at the 3-mm and K at 5-mm zones were signi fi cantly different [1.00(0.50-1.94) and 0.75(0.38-1.07) (p =0.011), 1.2 (0.65-2.30) and 0.70 (0.35-1.05) (p<0.001),1.5 (0.95-2.5) and 0.80(0.50-1.35) (p<0.001), 1.7 (0.75-2.93) and 0.90 (0.40-1.25) (p<0.001),respectively. Pterygium induced astigmatism of ≥1 D when it extended ≥2.25 mm onto the cornea (sensitivity 76.2%, speci fi city 66.7%). Conclusion Corneal extension is an important parameter in assessment of pterygium-induced astigmatism. Surgical intervention is recommended when the pterygium extends 2.25 mm or more onto the cornea. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />